THERAPEUTIC POTENTIAL OF THRIPHALA RASAYANA IN PRIMARY HYPERLIPIDEMIA- AN EXPERIMENTAL COMPARATIVE STUDY (International Journal of Ayurveda and Pharma Research, 2020)
Background: Elevated concentration of lipids in the blood is considered as the well-established and strong risk factor for cardiovascular disease. Primary hyperlipidaemia occurs solely due to interaction of mutated gene with unprecedented epidemiologic transitions associated with lifestyle changes and dietary patterns. Early detection and management of asymptomatic hyperlipidaemia is imperative to reduce the incidence of cerebrovascular, peripheral vascular and coronary artery diseases. Preferred screening test i.e. lipid panel test will be substantial on many levels including mortality, morbidity and staggering financial burden related with vascular endothelial dysfunction and atherosclerotic changes. Simple, low-cost and potential pharmacological interventions with Ayurveda drugs are highly beneficial in these preventable epidemics. The main ingredient, “Thriphala“ in the trial drug is considered as the best known rejuvenative (Rasayana) combination, which stimulate and correct the impaired inherent digestive capacity (Dhatwagni) by removing the inflammatory and obstructive causes (Srothorodha) associated with the dysfunctions in lipid metabolism. Objective: This study aims to evaluate the effect of an Ayurveda formulation on lipid level in patients with primary Hyperlipidaemia. It also ascertains the safety of the therapeutic formulation by evaluating the variations in the blood biochemical parameters. Methods: The study design was an experimental comparative study intended to compare the effect of potentiated Thriphalarasayana with standard anti-lipidemic drug in primary hyperlipidaemia. 29 cases in study group and 15 samples in control group participated in the trial. The data was analysed by using appropriate statistical techniques. Results: In the study group the values of total cholesterol, LDL and Atherogenic index shows more significant result than the control group receiving conventional anti-lipidemic drug. Conclusion: strategies for early detection and comprehensive management with Ayurveda formulations can be highly effective in reducing the global burden of vascular dysfunction related with hyperlipidaemia.